Zen shorts - Muth, Jon J. (New York : Scholastic Press, 2005)
When Stillwater the giant panda moves into the neighborhood, the stories he tells to three siblings teach them to look at the world in new ways. Includes factual note on Zen.
Keywords: Giant panda -- Fiction; Pandas -- Fiction; Brothers and sisters -- Fiction; Storytelling -- Fiction; Bears -- Juvenile fiction; Siblings -- Juvenile fiction; Storytelling -- Juvenile fiction